还有(a-b)x(b-a)^2(b-a)^3 =(m-n)^2(n-m)^15 =(ab^2)^2(-a^3 b)^3(-5ab) =(-5)^15 x (-2)^15 =
来源:学生作业帮助网 编辑:六六作业网 时间:2025/02/02 14:18:05
还有(a-b)x(b-a)^2(b-a)^3=(m-n)^2(n-m)^15=(ab^2)^2(-a^3b)^3(-5ab)=(-5)^15x(-2)^15=还有(a-b)x(b-a)^2(b-a)^
还有(a-b)x(b-a)^2(b-a)^3 =(m-n)^2(n-m)^15 =(ab^2)^2(-a^3 b)^3(-5ab) =(-5)^15 x (-2)^15 =
还有
(a-b)x(b-a)^2(b-a)^3 =
(m-n)^2(n-m)^15 =
(ab^2)^2(-a^3 b)^3(-5ab) =
(-5)^15 x (-2)^15 =
还有(a-b)x(b-a)^2(b-a)^3 =(m-n)^2(n-m)^15 =(ab^2)^2(-a^3 b)^3(-5ab) =(-5)^15 x (-2)^15 =
解 (a-b)x(b-a)^2(b-a)^3=-(b-a)(b-a)^2(b-a)^3=-(b-a)^6
(m-n)^2(n-m)^15=-(m-n)^17
(ab^2)^2(-a^3 b)^3(-5ab)=a^2b^4*-a^9b^3*(-5ab)=(5a^12)(b^8)
(-5)^15 x (-2)^15=5^15x 2^15=10^15
-(a-b)^6
(n-m)^17
5a^12 b^8
10^15
这个你解方程就可以了啊!
1,-(b-a)^6
2,(n-m)^15
3,a^2b^4(-a^9)b^3(-5ab)=3a^12b^8
4,[(-5)*(-2)]^15=10^15
因式分解:2x(a-b)-(b-a)
计算 a/a-b x (b-a/b)^2
[3(x+ y)^3-5(x+ y)^2-2x-2y]÷(x 还有一道,[(a+b)^3-2(a+b)^2+(a+b)]÷(a+b)
(a-b)^5x(b-a)^3+(a-b)^2x(a-b)^6
中学数学提问b/a+x/a+2=x/b-a/b(a不等于b)
-2a(a+b)+b(a+b)
(3x^/4y)^*2y/3y+x^2y^÷2y^/x 还有一个 (a+b/a-b)^*(2a-2b/3a+3b)-a^/a^-b^÷a/b
(3a+2b)(3a-2b)还有
因式分解(ab+b)^2-(a+b)^2还有一提(a^2-X^2)^2-4ax(x-a)^2
因式分解 (a-b)x+ax^2-b
(a+2b)(a-2b)+(a-b)(a+b)-2(a-3b)(a-b)
(a+b)/x-b/a=2+b/a(a+b≠0,a,b是常数)
(a+b).(a-b)
a/b-b/a
a+b>a-b,
因式分解 x^2+(a+b+c)x+(a+b)c
因式分解x^2+(a+b+c)x+(a+b)c
5(a*a*b-3*a*a*b)-2*(a*a*b-7*a*b*b)